Evaluation of perioperative complications in open and laparoscopic surgery for renal cell cancer with tumor thrombus involvement using the Clavien–Dindo classification. Issue 7 (July 2015) - Ebbing, J.; Wiebach, T.; Kempkensteffen, C.; Miller, K.; Bachmann, A.; Günzel, K.; Rieken, M.; Friedersdorff, F.; Baumunk, D.; Weikert, S.
Abstract Objective To identify risk factors for perioperative complications and morbidity in renal cell cancer (RCC) surgery with tumor thrombus invasion (TTI). Patients and methods Retrospective single-center analysis of 128 patients who underwent open (n = 97) or laparoscopic (n = 31) radical nephrectomy (NT) for RCC between 1999 and 2010. TTI was at Mayo-Level 0, I, II, III, IV in 88, 7, 10, 4, and 19 cases, respectively. Cavotomy was performed in 27, liver mobilisation in 20, and cardiovascular bypass in 17 patients. Results The rate of any early postoperative complication (PC) by Clavien–Dindo classification was 58.6%, while the severe early PC rate was 29.7%. There was a statistically significant difference in multivariate analysis in the incidence of any early PC and of severe early PC by Charlson score (OR:1.584 (95%CI:1.141–2.199), p = 0.006; OR:3.065 (95%CI:1.218–7.714), p = 0.017) and by tumor thrombus level TNM-UICC 2010 T3a/T3c (OR:10.668 (95%CI:1.266–89.871), p = 0.029; OR:10.502 (95%CI:2.981–36.992), p < 0.001). In pT3a cases open NT was associated with a higher early (57.9% vs. 25.8%) and severe (24.6% vs. 9.7%) PC rate compared to laparoscopic NT. The 30-day mortality rate was 0%. The 90-day mortality rate was 6.3% but 100% cancer-related. In Cox regression analysis tumor thrombus level was not predictive for overall survival. Conclusions The strongest risk factor for early and severe PC in patients with TTI is a supradiaphragmatic tumor thrombus. In cases with severe PC, this fact persists when comparing Mayo-Levels II–III and Level IV. In pT3a cases open NT shows a 2-fold higher early PC rate compared to laparoscopic NT.